TIME PRESSURE SEBAGAI PEMODERASI PENGHENTIAN PREMATUR PROSEDUR AUDIT TERHADAP KINERJA AUDITOR - Pemayun, Cokorda Istri Indraswari; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
This study aimed to test time pressure to moderate the effect of premature sign off of audit procedures on the performance of auditors. The sampling method in this research is to use saturated or census sampling method, involving all members of the population as a sample. The data in this study were collected through questionnaire method, ie by spreading questionnaire (questionnaire) to be filled or answered by respondents as many as 87 people on the auditor KAP in Bali Province. Testing the hypothesis in this study using moderated regression analysis (MRA). This research resulted in the premature sign off  of audit procedures that negatively affect the performance of auditors. This shows that the higher the premature sign off of audit procedures, the auditor's performance will decrease. Time pressure is able to weaken the influence of premature sign off  of audit procedures on the performance of auditors. This suggests that increasing the time pressure felt by the auditor, the behavior of premature termination of audit procedures will be reduced so that the auditor's performance is getting better.
Keywords: Premature Sign Off Procedures Audit, Performance Auditor, Time Pressure